Ocena i perspektywy rozwoju systemu terapeutycznego wykonywania kary pozbawienia wolności - Kwieciński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
This publication focuses on the problems of imprisonment relating to those sen-tenced with mental disorders, addicted to drugs or other means of intoxication, as well as the physically handicapped. The proposals in this work are based not only on the study of specialized literature and an analysis of legislative measures, but also on pilot studies in therapeutic wards all over Poland. In the conclusions the proposals de leg
Keywords: terapia; pozbawienie wolności; skazany; przymusowe leczenie; zaburzenia psychiczne